Needs, Rights and Democratic Renewal - Ife, Jim (Nouvelles pratiques sociales)

(untitled) (Université du Québec à Montréal, 2009)
The way in which a discourse of human needs has been appropriated by neo-liberal perspectives within modernity is well-documented. The construction and definition of “needs” by professionals has been criticised as “the dictatorship of needs”, and has readily excluded people other than professionals and managers from the definition of need. Need becomes objectified, something to be “assessed” by professionals using expert methodologies, rather than involving democratic participation. Here need becomes another excluding professional category, apparently objective and value-free, but in reality ideological. Furthermore, the deficit approach inherent in the idea of “need” runs counter to the more positive “strengths” approach of social work. “Rights” as an alternative to “needs” is superficially a more empowering discourse, and moving from a needs-based to a rights-based approach is therefore intuitively seductive, and has evidently appealed to social workers. However, ideas of “rights”, and especially “human rights” are also embedded within modernity and the privileging of the expert. The conventional discourse of human rights as defined by the UN or other legal bodies, applied universally, and protected through laws and legal institutions, is a negation of any democratic understanding of rights. “Human rights”, like need, thus becomes an objectified discourse of the powerful about the powerless. However the idea of human rights, if constructed from within a more postmodern framing, has the potential to move our understanding of a shared humanity beyond the constraints of modernity. Thus human rights per se is an inadequate, and potentially dangerous, formulation for progressive social work, unless democratic participation is restored to the human rights project. If human rights are understood as being embedded in a community of reciprocal rights and responsibilities, rather than as “things” possessed by individuals, human rights from below can become a powerful framework for the democratic renewal of practice.